A comparative study of vector control strategies for rotor-side converter of DFIG wind energy systems - Watcharin Srirattanawichaikul (2018)
© 2016 IEEE. This paper presents details comparisons between the stator-flux oriented and the voltage oriented control strategies for the doubly fed induction generator (DFIG) wind energy system. This paper develops a dynamic model of DFIG in the rotating reference frame, which is used to obtain the rotor current components into the generator torque and stator reactive power references using the both control strategies. Comparisons are made between both control strategies in terms of the stator flux and voltage position and also the stator power control. Finally, simulation studies are carried out on a 1-kW DFIG wind energy system. The validity of the performance and efficiency of the control strategies for variable wind speed are confirmed by the simulation results.